2021
DOI: 10.3390/pathogens10111411
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Oral Infection: Review of Methodological Aspects and Epidemiology

Abstract: Oral infection by Human Papillomavirus (HPV) has recently gained great attention because of its involvement in the development of a subset of head and neck squamous cell carcinoma. The role of specific Alpha-HPVs in this regard has been well established, whereas the contribution of other genera is under investigation. Despite their traditional classification as “cutaneous” types, Beta and Gamma HPVs are frequently detected in oral samples. Due to the lack of a standardized protocol, a large variety of methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 142 publications
(247 reference statements)
2
3
1
Order By: Relevance
“…In comparison to HPV 225, HPV 223 was less prevalent among this cohort which corroborates with our initial findings where the presence of HPV 223 and 225 were 0.97% and 9.7% in skin, respectively, among Caucasian subjects 9 . Prevalence of gamma‐HPV in mucosal epithelium‐like cervix, oral, and genital warts are previously reported in few studies where gamma‐HPVs were found either in a coinfected state with other HPVs or in an independent infectious state among Caucasian women and men 25–28 . In our study the prevalence of α‐HPV in oral mucosa of normal and diseased participants were found to be 7.3% and 26%, respectively, whereas, a previous study from our lab reported their prevalence to be 14% and 32% in normal and oral cancer patients respectively 29 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison to HPV 225, HPV 223 was less prevalent among this cohort which corroborates with our initial findings where the presence of HPV 223 and 225 were 0.97% and 9.7% in skin, respectively, among Caucasian subjects 9 . Prevalence of gamma‐HPV in mucosal epithelium‐like cervix, oral, and genital warts are previously reported in few studies where gamma‐HPVs were found either in a coinfected state with other HPVs or in an independent infectious state among Caucasian women and men 25–28 . In our study the prevalence of α‐HPV in oral mucosa of normal and diseased participants were found to be 7.3% and 26%, respectively, whereas, a previous study from our lab reported their prevalence to be 14% and 32% in normal and oral cancer patients respectively 29 .…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, prevalence of HPV 225 was predominantly seen in the keratinized epithelium, that is, the sun-exposed skin and breast skin of normal participants followed by previously reported in few studies where gamma-HPVs were found either in a coinfected state with other HPVs or in an independent infectious state among Caucasian women and men. [25][26][27][28] In our study the prevalence of α-HPV in oral mucosa of normal and diseased participants were found to be 7.3% and 26%, respectively, whereas, a previous study from our lab reported their prevalence to be 14% and 32% in normal and oral cancer patients respectively. 29 Although, diseased participants showed more α-HPV prevalence in their oral mucosa but coinfection with HPV 223 was found in a single normal participant and HPV 225 was present in two normal participants only.…”
Section: Discussioncontrasting
confidence: 78%
“…The keratinized penis epithelium is more resistant to HPV infection, and the amount of biological fluid that reaches the oropharynx can also be a factor in this gender difference [ 30 ]. Finally, it appears that women develop a stronger systemic immune response than men after a genital HPV infection [ 31 ]. This would more efficiently protect women than men in the case of subsequent exposure to HPV.…”
Section: Oral–cervical–perinatal Hpv Transmissionmentioning
confidence: 99%
“…In women aged 18 to 69 years, data from oral and cervicovaginal HPV DNA screening showed that cervicovaginal HPV infection was present in 45.2%, oral HPV infection in 4.1%, double infection in 3.0%, and concordant infection in 1.1%. Nearly half of U.S. men have HPV infection of the penis [ 31 ]. High burden of HPV infection of the penis has been associated with oral HPV infection.…”
Section: Oral–cervical–perinatal Hpv Transmissionmentioning
confidence: 99%
“…Human papilloma virus (HPV) infection is a risk factor for carcinoma in the oropharyngeal, genital, and anal regions [15,16]. Especially the high-risk (hr) HPV alpha types HPV-16 and − 18 are commonly encountered in mucosal carcinomas [17]. High prevalence of gynecologic HPV infections has been detected in females with CHH [18].…”
Section: Introductionmentioning
confidence: 99%